Drawing the Line Between Lay and Expert Opinion Evidence - Chin, Jason; Tomiska, Jan; Li, Chen (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2017)
This article examines the vanishingly thin line between lay and expert opinion evidence in Canada. In Parts I and II, we set the stakes — the dangers involved in expanding the scope of admissible opinion evidence. Canadian trial courts have been warned by peak scientific bodies and public commissions like the Goudge Inquiry about the dangers of attorning to persuasive expert witnesses. Thus, expert evidence faces new hurdles, both substantively and procedurally. This scrutiny has inspired parties to seek refuge in the more flexible and discretionary lay opinion evidence rules. But newfound vigilance to expert opinion is invalidated if the same evidence can be admitted as lay opinion. Parts III and IV illustrate these problems as we examine three cases in which authoritative lay witnesses opined on topics requiring specialized training and expertise. Three hazards are readily apparent from this analysis: (1) the lay witnesses opined on matters in which there are established methodologies to control for unconscious bias, but did not follow these methodologies; (2) the lay witnesses–– police officers––though authority figures, were not qualified experts in the area they were opining on, and; (3) the lay opinion jurisprudence has failed to meaningfully distinguish between lay and expert opinion. In Part V, we seek to fill this void by proposing a new analytic approach—Lay Opinion 2.0—which draws on both the practical and epistemological distinction between lay and expert opinion to provide an efficient and fair test for the admission of lay opinion evidence.